Reserve Estimation of Silica Sand Deposits by Core Control and Geophysical Methods, A Case Study from Saudi Arabia - Alsulaimani, G.; Ahmed, M. F.; Raza, M. A. (The Nucleus, 2016)
This paper summarizes a study carried out for the reserve estimation of silica sand deposits by core control and geophysical data in southern Dawmat Al Jandal, Al Jawf in Saudi Arabia. The study demonstrates the comparison of the data acquired from both core control and geophysical methods. The geophysical techniques applied for this study included the Ground penetrating radar (GPR) and multichannel analysis of surface waves (MASW) to estimate the thickness of surficial silica sand deposits in the study area. The GPR survey acquired 1620 linear meters of ground data across the tape to image internal reflections within the sand deposits up to the contact with underlying sandstone along with 27 MASW field records acquired at different locations by generating 1-D and 2-D shear wave velocity profiles. The results obtained from both of the geophysical investigation techniques were satisfactory and further validated with the core holes data and values.